Agricultural Sector Risk Assessment : Methodological Guidance for Practitioners - World Bank (World Bank, Washington, DC, 2016)
In the agricultural sector, risks are inherent and ubiquitous, posing potentially serious consequences for stakeholders and consumers. Risks disrupt supply chains, causing extensive financial and economic losses. Agricultural risks are also the principal cause of transient food insecurity, creating a poverty trap for millions of households across the developing world that enforces a vicious cycle of shock and recovery. Climate change is exacerbating this cycle by shifting the frequency and intensity of weather related risks and increasing uncertainty. Effective agricultural risk management (ARM) is crucial to increasing economic growth, improving food security, and reducing poverty. Although levels of risk vary within and between countries, lower-income and highly agriculture-dependent countries are more vulnerable to agriculture-related risks. In these countries, there is an urgent need to better assess risks, understand the interconnections between different types of risk, and improve agricultural risk management strategies.